PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Pegawai Bank Jateng Se-Kota Semarang) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to identify and analyze the impact of leadership and motivation towards Bank Jateng employees performance in Semarang, and job satisfaction as an intervening variable. This research is a quantitative research using analytical survey approach. The Population of this research are Bank Jateng employees in the city of Semarang, Central Java. The sampling method used in this research is purposive sampling technique, and the obtained sample was 134. Data collection using Likert scale 1-5 closed questionnaire. Data were analyzed using multiple linear regression and path analysis. The results showed that: leadership and motivation have significant positive impact on job satisfaction of employees at the Bank Jateng in Semarang. Leadership, motivation and job satisfaction have significant positive effect on the performance of employees at the Bank Jateng in Semarang. Job satisfaction is not as an intervening variable in the relationship between leadership and motivation towards Bank Jateng employees performance in Semarang. Key Word: impact of leadership, motivation, job satisfaction, and employees performance